Sleep disturbance and neurocognitive outcomes in older patients with breast cancer: Interaction with genotype. Issue 24 (25th September 2019) - Carroll, Judith E.; Small, Brent J.; Tometich, Danielle B.; Zhai, Wanting; Zhou, Xingtao; Luta, George; Ahles, Tim A.; Saykin, Andrew J.; Nudelman, Kelly N. H.; Clapp, Jonathan D.; Jim, Heather S.; Jacobsen, Paul B.; et al.
Abstract : Background: Sleep disturbance and genetic profile are risks for cognitive decline in noncancer populations, yet their role in cancer‐related cognitive problems remains understudied. This study examined whether sleep disturbance was associated with worse neurocognitive outcomes in breast cancer survivors and whether sleep effects on cognition varied by genotype. Methods: Newly diagnosed female patients (n = 319) who were 60 years old or older and had stage 0 to III breast cancer were recruited from August 2010 to December 2015. Assessments were performed before systemic therapy and 12 and 24 months later. Neuropsychological testing measured attention, processing speed, executive function, learning, and memory; self‐perceived cognitive functioning was also assessed. Sleep disturbance was defined by self‐report of routine poor or restless sleep. Genotyping included APOE, BDNF, and COMT polymorphisms. Random effects fluctuation models tested associations of between‐person and within‐person differences in sleep, genotype, and sleep‐genotype interactions and cognition and controlled for age, reading level, race, site, and treatment. Results: One‐third of the patients reported sleep disturbances at each time point. There was a sleep‐ APOE ε4 interaction ( P = .001) in which patients with the APOE ε4 allele and sleep disturbances had significantly lower learning and memory scores than those who were APOE ε4‐negative and without sleep disturbances. There was also a sleep disturbance– COMT genotype interaction ( P = .02) in which COMT Val carriers with sleep disturbances had lower perceived cognition than noncarriers. Conclusions: Sleep disturbance was common and was associated with worse cognitive performance in older breast cancer survivors, especially those with a genetic risk for cognitive decline. Survivorship care should include sleep assessments and interventions to address sleep problems. Abstract : This study reports that sleep disturbances in breast cancer survivors are related to worse self‐perceived cognitive functioning and learning and memory performance, especially in those with a genetic risk (eg, APOE ε4) for cognitive decline.